2010
DOI: 10.1002/hed.21357
|View full text |Cite
|
Sign up to set email alerts
|

Induction of laryngeal cancer cell death by Ent‐11‐hydroxy‐15‐oxo‐kaur‐16‐en‐19‐oic acid

Abstract: 5F induces apoptosis of laryngeal cancer cells by inhibiting NF-κB activation/induction, suppressing pro-proliferative and anti-apoptotic molecules, and promoting pro-apoptotic Bax.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Ent-11-hydroxy-15-oxo-kaur-16-en-19-oic acid (5F) is  an active compound in Pteris semipinnata L (PsL) [4][5][6] . Earlier studies from our laboratory demonstrated 5F could inhibit the in vitro growth of a number of tumors (e.g., colorectal cancer, gastric cancer, anaplastic thyroid carcinoma, liver cancer and laryngeal cancer) via a mitochondrial-mediated apoptotic mechanism [7][8][9][10][11] . We have also compared 5F with 7-hydroxystaurosporine (UCN01), which is currently being evaluated in clinical trials as an antitumor drug in the United State and Japan [12,13] .…”
Section: Introductionmentioning
confidence: 99%
“…Ent-11-hydroxy-15-oxo-kaur-16-en-19-oic acid (5F) is  an active compound in Pteris semipinnata L (PsL) [4][5][6] . Earlier studies from our laboratory demonstrated 5F could inhibit the in vitro growth of a number of tumors (e.g., colorectal cancer, gastric cancer, anaplastic thyroid carcinoma, liver cancer and laryngeal cancer) via a mitochondrial-mediated apoptotic mechanism [7][8][9][10][11] . We have also compared 5F with 7-hydroxystaurosporine (UCN01), which is currently being evaluated in clinical trials as an antitumor drug in the United State and Japan [12,13] .…”
Section: Introductionmentioning
confidence: 99%
“…The activation of EGFR is a frequent event in HNSCC, and has provided the molecular basis for current efforts aimed at evaluating the clinical activity of EGFR inhibitors in HNSCC [21], [22]. However, to date, the role of EGFR-dependent NFκB in the functional orchestration of HNSCC progression and metastasis is poorly realized [22], [23]. Since NFκB is able to regulate more than 150 genes, and is able to functionally orchestrate many steps in carcinogenesis, tumor progression and metastasis, it is important to delineate the efficacy of potential EGFR-TK inhibitors that target the NFκB-dependent HNSCC cell survival advantage.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, 5F possesses seven chiral atoms, the configuration of which, as obtained by anomalous dispersion, is R-C4, S-C5, R-C8, S-C9, R-C12 and R-C15 (6). Previous studies have reported that 5F induces apoptosis in and inhibits the proliferation of lung, liver, anaplastic thyroid, stomach, colon and throat cancer cells (7)(8)(9)(10)(11) However, whether 5F exerts anti-tumor effects during the progression of breast cancer remains unclear. The present study examined the functions of 5F in the growth and apoptosis of three breast cancer cell lines, including MDA-MB-231, MCF-7 and SK-BR-3.…”
Section: Introductionmentioning
confidence: 99%